TERATOGENIC RISKS AND CLINICAL JUSTIFICATIONS: A REVIEW OF ANTIBIOTIC ADMINISTRATION IN EARLY PREGNANCY - Alina Mihaela Calin; Alina Plesea Condratovici; Magdalena Miulescu; Ludmila Vaschevici; Anamaria Zaharescu; Lorenza Forna; Simona Manuela Bida (Romanian Journal of Oral Rehabilitation)
The first trimester of pregnancy represents a critical window for embryonic development, during which drug exposure may lead to teratogenic effects. Antibiotics are commonly prescribed to treat maternal infections that, if left untreated, can result in severe outcomes for both the mother and fetus. However, the decision to initiate antibiotic therapy during early pregnancy must weigh the clinical necessity against potential fetal risks. This review evaluates the teratogenic potential of commonly used antibiotics, highlights pharmacokinetic changes in early gestation, and examines therapeutic options for frequently encountered infections. Safe antibiotic classes, such as penicillins and cephalosporins, are contrasted with those requiring caution, including tetracyclines, fluoroquinolones, and sulfonamides. Ethical considerations, including informed consent and individualized risk assessment, are also discussed. In addition, the paper identifies key gaps in current knowledge and emphasizes the need for future research through pregnancy registries, pharmacovigilance, and prospective studies. Ultimately, the judicious use of antibiotics, based on current evidence, clinical guidelines, and patient engagement, can optimize outcomes and protect both maternal and fetal health in early pregnancy.